An assessment of how bio-E10 will impact the vehicle-related ozone contamination in China. (November 2020) - Zhang, Mengzhu; Ge, Yunshan; Wang, Xin; Thomas, Daisy; Su, Sheng; Li, Hu
Abstract: Bio-E10 is short for the biofuel made up of 90% gasoline in volume and 10% bio-ethanol, which is the ethanol made from commercially-grown crops such as corn and wheat by the sugar fermentation process. In China, bio-E10 will be supplied nationwide from 2020 as an alternative to conventional gasoline, aiming at ensuring greater energy security and lowering the greenhouse gas emissions. In order to assess the impacts of the upcoming bio-E10 application on the ozone forming potential (OFP) of the emissions from in-use vehicles, this paper examined the carbonyls and volatile organic compounds (VOCs) in the evaporative and tailpipe emissions of three China-4 certified in-use vehicles fueled with a market-available gasoline and two match-blend bio-E10s, and calculated their OFPs using the Maximum Incremental Reactivity (MIR) method. The results revealed that for the evaporative emissions, the use of bio-E10s increased the carbonyl and VOC emissions released within the diurnal-loss stage by 8.5–17.6% and 11.1–78.6% respectively, but decreased the carbonyl and VOC emissions in the hot-soak stage by 47.4%–61.5% and 4.8%–20.6% respectively. Regarding the tailpipe emissions, in comparison to the gasoline baseline, burning bio-E10s increased the carbonyls by 15%–46% while reducing the VOCs by 37%–56% over the New European Driving Cycle (NEDC). Reductions in the tailpipe OFPs up to 47.3% were seen with the application of the bio-E10s, however, there were no clear conclusions with respect to the evaporative OFPs, which varied from −15% to ＋25% compared to the gasoline baseline. Based on the test results and census data, the application of bio-E10 in China is shown to help remove part of ozone contamination from the in-use vehicle sector.